Cross-Reactivity Between Antigens of Coccidioides immitis, Histoplasma capsulatum, and Blastomyces dermatitidis in Lymphocyte Transformation Assays - Cox, Rebecca A. (1979)
The cross-reactivity of four Coccidioides antigens, three Histoplasma antigens, and two Blastomyces antigens were determined in lymphocyte transformation assays of 11 coccidioidin-reactive, histoplasmin-nonreactive subjects (group I), 13 coccidioidin-nonreactive, histoplasmin-reactive persons (group II), and 13 subjects who were skin test negative to both antigens (group III). Mycelial and yeast (or spherule)-phase antigens of the three fungi were included. Significant cross-reactivity was obtained with both coccidioidins, spherulin, and the alkali-soluble, water-soluble cell wall antigen of C. immitis, to the extent that the responses of histoplasmin-reactive persons were not statistically different (P > 0.05) from those of coccidioidin-reactive persons. In contrast, optimal dilutions of Histoplasma mycelial and yeast-phase lysates effectively distinguished (P < 0.01) responses of histoplasmin- and coccidioidin-reactive persons. The alkali-soluble cell wall antigen of H. capsulatum showed extensive cross-reactivity at most concentrations and was markedly stimulatory to lymphocytes of skin test-negative persons. Blastomycin elicited significant cross-reactions in histoplasmin-sensitive subjects and to a lesser extent in coccidioidin-sensitive subjects. The alkali-soluble cell wall antigen cross-reacted in cultures of histoplasmin-reactive persons but not in those of coccidioidin-reactive persons. All antigens effectively distinguished (P < 0.001) homologous responses of skin test-positive persons (groups I and II) from those of skin test-negative persons (group III). The extensive cross-reactivity in lymphocyte transformation assays in the absence of cross-reactivity in skin tests suggests that these two immune responses may be mediated by different T lymphocyte populations, may be elicited by different antigenic components, or both.